Resilient roots: sustainable landscape design for Colorado's Front Range residences - Mosbarger, Olivia, author (Colorado State University. Libraries, 2024)
My Honors Thesis, Resilient Roots: Sustainable Landscape Design for Colorado's Front Range Residences, is an accumulation of the skills that I have learned in my landscape design studios throughout my time here at Colorado State University, as well as the addition of knowledge that I have gained in my horticulture, irrigation, entomology, and turfgrass studies. Specifically, I focused on sustainability in Western residential landscapes and how each of these topics (horticulture, irrigation, entomology, turfgrass, etc) can be utilized to help create a more drought-tolerant environment through design. I designed a construction plan for an ideal sustainable residential landscape, which can act as a guide for what methods, plants, and materials are beneficial for the Front Range’s climate and natural resources. I also designed an irrigation plan, a planting schedule, and a 3D model to best represent how this plan will look and work for the clients.
Keywords: sustainability; landscape; design; irrigation; horticulture; entomology; turfgrass; SketchUp; Lumion; AutoCAD